An analysis of the African cancer research ecosystem: tackling disparities. Issue 2 (15th February 2023) - Rubagumya, Fidel; Carson, Laura; Mushonga, Melinda; Manirakiza, Achillle; Murenzi, Gad; Abdihamid, Omar; Athman, Abeid; Mungo, Chemtai; Booth, Christopher; Hammad, Nazik
Abstract : Disparities in cancer research persist around the world. This is especially true in global health research, where high-income countries (HICs) continue to set global health priorities further creating several imbalances in how research is conducted in low and middle-income countries (LMICs). Cancer research disparities in Africa can be attributed to a vicious cycle of challenges in the research ecosystem ranging from who funds research, where research is conducted, who conducts it, what type of research is conducted and where and how it is disseminated. For example, the funding chasm between HICs and LMICs contributes to inequities and parachutism in cancer research. Breaking the current cancer research model necessitates a thorough examination of why current practices and norms exist and the identification of actionable ways to improve them. The cancer research agenda in Africa should be appropriate for the African nations and continent. Empowering African researchers and ensuring local autonomy are two critical steps in moving cancer research towards this new paradigm.